1994
DOI: 10.1097/00000658-199407000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Squamous Cell Carcinoma of the Anal Canal Predictors of Initial Treatment Failure and Results of Salvage Therapy

Abstract: ObjectiveThe outcomes of patients with squamous cell carcinoma of the anal canal treated by either sphincter-preserving procedures or radical surgery were evaluated, with the goals of identifying factors predicting treatment failure and quantifying results of salvage therapy in patients with recurrent disease. Basic ProceduresA population-based study on all patients in all 159 hospitals of the Department of Veterans Affairs (VA) from 1987 to 1991 was carried out. Data were compiled from several national comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
6

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(46 citation statements)
references
References 32 publications
3
36
0
6
Order By: Relevance
“…In the present study, six of the 16 patients who underwent appropriate surgical treatment survived for more than 10 years. These results are similar to those of Longo et al [20] , who reported a survival rate of 53% among 17 patients and Ellenhorn et al [21] , who noted that 44% of 38 patients survived for 5 years after salvage resection.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, six of the 16 patients who underwent appropriate surgical treatment survived for more than 10 years. These results are similar to those of Longo et al [20] , who reported a survival rate of 53% among 17 patients and Ellenhorn et al [21] , who noted that 44% of 38 patients survived for 5 years after salvage resection.…”
Section: Discussionsupporting
confidence: 90%
“…In 2 different studies, Nigro [16] and Flam et al [19] recommended a second course of CRT for patients with macroscopic disease. In the study of Longo et al [20] , salvage CRT has been shown to have 19% of survival rate, while Flam et al [21] reported a 50% survival. On the other hand, other studies showed 5-year survival rates after APR ranging from 30 to 60% [22,23] .…”
Section: Oncological Results Of Surgical Salvage Surgerymentioning
confidence: 99%
“…Devido a este fato, ao tipo de cirurgia mutiladora necessária para ressecção destes tumores com conseqüente colostomia definitiva e aos bons resultados observados em outras neoplasias espinocelulares, como nos tumores de laringe, a quimioterapia e a radioterapia tornaramse o tratamento de eleição destes doentes. Após o término do tratamento, a lesão local deve ser avaliada; se persistente deverá, então, ser ressecada cirurgicamente (21,23,30) . A principal droga quimioterápica usada tem sido a 5-FU combinada com a mitocina e/ou cisplatina por 4 a 5 dias (9,24,28,29,30,32,33) .…”
Section: Discussionunclassified